Effectiveness of platelet concentrates in the treatment of temporomandibular disorders - Heber Isac Arbildo Vega; Víctor Alay Baca; Gustavo Alfredo Alberto Giribaldi Ugáz; Hernán Vásquez Rodrigo (Editorial Ciencias Médicas, 2021)
Introduction: Temporomandibular disorders are a group of dysfunctions which affect the temporomandibular joint and/or associated musculoskeletal tissues. Objective: Determine the effectiveness of platelet concentrates in the treatment of temporomandibular disorders. Methods: A bibliographic search was conducted from January 2014 to April 2019 in the biomedical databases PubMed, Embase, SciELO, Scopus, Science Direct, System for Information on Gray Literature in Europe, Latin American and Caribbean Health Sciences Literature, Google Scholar, and Cochrane Central Register of Clinical Trials. The following selection criteria were defined for the studies: randomized clinical trials published in the last five years and reporting on the effectiveness (pain reduction and maximum opening increase) of platelet concentrates in the treatment of temporomandibular disorders. Bias risk analysis was based on the Cochrane manual of systematic reviews of interventions. Results: Nine papers were retrieved, of which 100% reported no differences in pain reduction or maximum opening increase resulting from the use of platelet concentrates in the treatment of temporomandibular disorders. Conclusions: The literature review conducted suggests that there is slight evidence of the potential benefits of intra-articular injections of platelet concentrates in patients with temporomandibular disorders. However, a standardized protocol should be established for the preparation and application of these concentrates.